Libertad de conciencia en los contrayentes del matrimonio civil. Los casos de simpatizantes en el Líbano, Baraya y el de presbiterianos en Medellín, Ca. 1894-1919 (2005)
ABSTRACT: In this article intends to give answer to the way as the practice of the civil marriage contributed to the fragmentation of the Colombian religious field, in an epoch in which the country was governed for a Constitution that gave supremacy to the Roman Catholic Church and had a Concordat with the Saint Yields, which offered him to be able al catholic clergy on the public instruction and the religious practices. Which they were the legal instruments by which the Protestants managed to legalize its marriages, a custom that established rules and had an important social function in the protestant Churches, with an almost life and permanent relation? Of what way supporters of the protestantism as the Protestants fought for their liberty of conscience?